(untitled) (Research, Society and Development, 2020)
The current economic and global scenario presents constant changes, the apparel sector is in a continuous process of growth in the formal and mainly informal sectors, stimulating market competition, offering customers a wide variety of options for consumption, starting from this premise customers are becoming more demanding in the search for a quality service, that present a differential that meets their expectations. The present article sought to analyze the quality of care in the apparel trade in the city of Currais Novos - RN. In order to do so, a survey was initially carried out on Service Marketing and Customer Service, followed by a questionnaire with 04 (four) groups with participants aged between 09 (nine) and 60 (sixty) years. Thus, it is a qualitative case study with questionnaire application by e-mail. Through the results of the surveys, it was informed that the employee does not identify the client’s needs, meet by means of people’s acceptance, as well as the lack of qualification. The study concludes that the quality of service in the city of Currais Novos presents an unpreparedness to know its products and customers through its employees.